Lire les effets de voix - Dominique Rabaté (Sillages Critiques)
This article concerns questions of voice, enunciation and the narrator in the works of Louis-René des Forêts, Samuel Beckett, Albert Camus, Henri Michaux, Fyodor Dostoyevsky,et al.